2014
DOI: 10.1155/2014/467452
|View full text |Cite
|
Sign up to set email alerts
|

RNA Viruses: ROS-Mediated Cell Death

Abstract: Reactive oxygen species (ROS) are well known for being both beneficial and deleterious. The main thrust of this review is to investigate the role of ROS in ribonucleic acid (RNA) virus pathogenesis. Much evidences has accumulated over the past decade, suggesting that patients infected with RNA viruses are under chronic oxidative stress. Changes to the body's antioxidant defense system, in relation to SOD, ascorbic acid, selenium, carotenoids, and glutathione, have been reported in various tissues of RNA-virus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
238
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(268 citation statements)
references
References 211 publications
6
238
0
6
Order By: Relevance
“…Similarly, previous observations showed that oxidative stress is responsible for the induction of apoptosis in several cell types, including natural killer cells, enterocytes, podocytes, and astrocytes, during HIV-1 infection (44,(48)(49)(50). Recent studies, such as those conducted by Kalinowska et al (14) and Trautmann et al (16), also showed that decreased IL-7-induced pSTAT5 levels in CD8 T cells during HIV-1 infection were associated with oxidative stress.…”
Section: Ccr7mentioning
confidence: 62%
“…Similarly, previous observations showed that oxidative stress is responsible for the induction of apoptosis in several cell types, including natural killer cells, enterocytes, podocytes, and astrocytes, during HIV-1 infection (44,(48)(49)(50). Recent studies, such as those conducted by Kalinowska et al (14) and Trautmann et al (16), also showed that decreased IL-7-induced pSTAT5 levels in CD8 T cells during HIV-1 infection were associated with oxidative stress.…”
Section: Ccr7mentioning
confidence: 62%
“…This was first shown for the Sendai virus model and mouse splenocytes, which enhance the production of FR in response to contact with the virus, not only intact, but also inactivated by ultraviolet irradiation [49]. Later the increase of oxidative activity in cells leading to their death was shown for many viruses, both RNA and DNA genomic [44,50,52].…”
Section: Suppression Of Virus Reproduction Due To Antioxidant Activitymentioning
confidence: 90%
“…[4][5][6][7][8] Relationships between viruses and DDR in the host are well described and show that viruses modulate cell metabolism and interact with cellular molecules to activate or deactivate different pathways in DNA damage repair. [9][10][11][12] Virus-induced dysfunction in DNA repair may result from up-or downregulation of key factors involved in DDR. There is also growing evidence that HIV-1 influences DDR during active infection, with most studies focusing on the accessory protein Vpr targeting different factors essential for host genome integrity and cell cycle arrest.…”
Section: Introductionmentioning
confidence: 99%